MR angiography at 3 T of peripheral arterial disease: a randomized prospective comparison of gadoterate meglumine and gadobutrol - Loewe, Christian; Haneder, Stefan (American journal of roentgenology, 2015)
Objective: This large-scale randomized study aimed to show the noninferiority in terms of diagnostic performance of gadoterate meglumine-enhanced versus gadobutrol-enhanced 3-T MR angiography (MRA) using digital subtraction angiography (DSA) as the reference standard in patients with peripheral arterial occlusive disease (PAOD). Subjects and methods: In this prospective international randomized double-blind phase IV trial, 189 patients were enrolled. Of them, 156 could be included in the per-protocol population for on-site assessments and 154 for off-site readings. Subjects underwent peripheral MRA, after injection of 0.1 mmol/kg of either gadoterate meglumine or gadobutrol, and DSA within 30 days. The diagnostic accuracy was evaluated and compared using a noninferiority analysis. Secondary endpoints included sensitivity, specificity, diagnostic confidence, contrast-to-noise ratio, and signal-to-noise ratio evaluations. Results: The percentage agreement between MRA and DSA for stenosis detection was similar for on-site readings for both groups (mean ± SD, 80.6% ± 16.1% with gadoterate meglumine vs 77.1% ± 19.6% with gadobutrol; 3.5% difference), and the same was true for off-site readings (73.9% ± 16.9% with gadoterate meglumine vs 75.1% ± 13.8% with gadobutrol; 1.1% difference). The noninferiority of gadoterate meglumine to gadobutrol was shown for both on- and off-site readings. Sensitivity in detecting significant stenosis (> 50%) was 72.3% for gadoterate meglumine versus 70.6% for gadobutrol, whereas specificity (92.6% vs 92.3%), diagnostic confidence (87.0% vs 86.0%), signal-to-noise ratio (165.5 vs 161.0), and contrast-to-noise ratio (159.5 vs 155.3) did not differ statistically significantly between the two groups. Conclusion: Gadoterate meglumine was found to be not inferior to gadobutrol in terms of diagnostic performance in patients with PAOD undergoing 3-T contrast-enhanced MRA. No statistically significant differences were detected between the two MRA groups.